Tectonic Activity Response Based on Geomorphic Index In Pasirmunjul, Sukatani, Purwakarta Regency, West Java - Pradifta, Alif; Ismawan, Ismawan; Ramadian, Aldrin (Faculty of Geological Engineering, Universitas Padjadjaran, 2022)
The study area administratively located in Sukatani sub-district, Purwakarta Regency, West Java. This study is aim to determine the level of tectonic activity in the study area using a quantitative geomorphological approach. The geomorphic indices that used in this research are the Mountain Front Sinusity (SMF), Ratio of valley floor width to valley height (Vf), Hipsometric Integral (HI), Drainage Basin Shape (BS), and Asymmetry Factor (AF). Then, these parameters of geomorphic index, are included in the calculation of the Relative Tectonic Activity Index (IATR) which is show the distribution of tectonic activity levels in the study area. The results of the analysis Relative Tectonic Activity Index (IATR) show that the study area is divided into 3 classes of tectonic activity, namely class 2 (high), class 3 (medium), and class 4 (low). Class 2 occupies about 19.5% of the study area with an area of 7.6 km2 which is spread over the western part of the study area. Class 3 occupies about 79.8% of the study area with an area of 31.4 km2 which is spread dominantly in the study area. While class 4 (low), which occupies about 0.7% of the study area with an area of 0.28 km2 which is spread in the northern part of the research area. In general, the study area has a fairly balanced between level of tectonic activity with an erosion activity, but in the western part of the study area tended to be more dominated with tectonic activity than the erosion activity, which was indicated due to the influence of the structure in the area and caused a catastrophic ground motion in surrounding area.